login
A111669
Triangle read by rows, based on a simple Fibonacci recursion rule.
4
1, 1, 1, 1, 2, 1, 1, 3, 4, 1, 1, 4, 11, 7, 1, 1, 5, 26, 32, 12, 1, 1, 6, 57, 122, 92, 20, 1, 1, 7, 120, 423, 582, 252, 33, 1, 1, 8, 247, 1389, 3333, 2598, 681, 54, 1, 1, 9, 502, 4414, 18054, 24117, 11451, 1815, 88, 1, 1, 10, 1013, 13744, 94684, 210990, 172980, 49566, 4807, 143, 1
OFFSET
0,5
COMMENTS
Subdiagonal is A000071(n+3). Row sums of inverse are 0^n.
Row sums are given by A135934. - Emanuele Munarini, Dec 05 2017
LINKS
FORMULA
T(n, k) = T(n-1, k-1) + F(k+1)*T(n-1, k) where F(n)=A000045(n).
Column k has g.f. x^k/Product_{j=0..k} (1 - F(j+1)*x).
EXAMPLE
Triangle begins
1....1....2....3....5....8...13....F(k+1)
1
1....1
1....2....1
1....3....4....1
1....4...11....7....1
1....5...26...32...12....1
1....6...57..122...92...20....1
For example, T(6,3) = 122 = 26 + 3*32 = T(5,2) + F(4)*T(5,3).
MATHEMATICA
(* To generate the triangle *)
Grid[RecurrenceTable[{F[n, k] == F[n-1, k-1] + Fibonacci[k+1] F[n-1, k], F[0, k] == KroneckerDelta[k]}, F, {n, 0, 10}, {k, 0, 10}]] (* Emanuele Munarini, Dec 05 2017 *)
PROG
(PARI) T(n, k) = if ((n<0) || (k<0), 0, if ((n==0) && (k==0), 1, T(n-1, k-1) + fibonacci(k+1)*T(n-1, k))); \\ Michel Marcus, May 25 2024
CROSSREFS
KEYWORD
easy,nonn,tabl
AUTHOR
Gary W. Adamson, Aug 14 2005
EXTENSIONS
Edited by Paul Barry, Nov 14 2005
STATUS
approved